Job Satisfaction In Hotel Employees: A Systematic Review Of The Literature - da Borralha1, Sérgio; de Jesus, Saul Neves; Pinto, Patrícia; Viseu, João (Journal of Tourism, Sustainability and Well-being, 2017)
Hotel employees’ job satisfaction is very important to their performance. In a systematic review of the previous literature on hotel employees, it was found that the most studied variable was job satisfaction; there were no other systematic reviews on the topic. In this review, performed in the Web of Knowledge, Web of Science (Social Sciences Index Expanded, Social Sciences Citation Index, Medline), and Science Direct between 2000 and 2014, 51 studies were found. These studies indicated that satisfaction is crucial to the financial performance and prosperity of hotels and acts a mediator in customer satisfaction. Contributing to greater satisfaction are factors such as greater autonomy and independence, greater power of decision making, flexible schedules, better working conditions, and training. The factors that promote dissatisfaction are wages and reduced benefits. The studies also indicated that a higher level of job satisfaction can have a direct impact on increasing the financial performance of the hotel. The implications of this study for hoteliers and directors relates to the creation of adequate working conditions to increase job satisfaction and provide hotel employees with a greater sense of subjective well-being.